THE REALITY OF LANGUAGE - Indrawati, - (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2010)
Language possesses a very significant role in the formation of reality inside the mind of its users. Three elements comprising of society, language, and thoughts are interrelated in constructing the reality of language in society. Society produces thoughts; thoughts create society, and language mediates the process of formulation of reciprocal relation between thoughts and society. Sexism in language use in society prevails in favours of men culture that is directly responsible for the way people see their world, as an important means of reinforcing sexist assumptions. As life flows to its natural course, this linguistic habit is challenged in its being rational and logical by linguistic feminists, of which both female and male. Keywords: sexism in language, linguistic feminists